2019
DOI: 10.3390/ijms20174101
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Pharmacological Potential of Boswellic Acids against Chronic Diseases

Abstract: Natural compounds, in recent years, have attracted significant attention for their use in the prevention and treatment of diverse chronic diseases as they are devoid of major toxicities. Boswellic acid (BA), a series of pentacyclic triterpene molecules, is isolated from the gum resin of Boswellia serrata and Boswellia carteri. It proved to be one such agent that has exhibited efficacy against various chronic diseases like arthritis, diabetes, asthma, cancer, inflammatory bowel disease, Parkinson’s disease, Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 224 publications
(231 reference statements)
0
122
0
Order By: Relevance
“…Since its Low production of leukotriene is the main target achieved as an anti-inflammatory agent. Additional, comprehensive inquiries exhibited Boswellia acids as non-redox inhibitors, which might provide a site for pentacyclic triterpenes on 5-LOX (Roy et al, 2019). Henkel et al (2015) demonstrated that the anti-inflammatory mechanism of BAs was related to the inhibition of antimicrobial peptide LL-37.…”
Section: Pharmacological Properties Of Boswellia Acidsmentioning
confidence: 99%
“…Since its Low production of leukotriene is the main target achieved as an anti-inflammatory agent. Additional, comprehensive inquiries exhibited Boswellia acids as non-redox inhibitors, which might provide a site for pentacyclic triterpenes on 5-LOX (Roy et al, 2019). Henkel et al (2015) demonstrated that the anti-inflammatory mechanism of BAs was related to the inhibition of antimicrobial peptide LL-37.…”
Section: Pharmacological Properties Of Boswellia Acidsmentioning
confidence: 99%
“…It is used as herbal medicine to treat arthritis and cardiovascular diseases in its traditional applications . A series of pentacyclic triterpenes boswellic acids have been well characterized as major active constituents . For example, 11‐keto‐β‐boswellic acid (KBA), acetyl‐11‐keto‐β‐boswellic acid (AKBA) and β‐boswellic acid (BBA) have shown to inhibit 5‐lipoxygenase and microsomal prostaglandin E synthase‐1 or the serine protease cathepsin G .…”
Section: Introductionmentioning
confidence: 99%
“…[7] A series of pentacyclic triterpenes boswellic acids have been well characterized as major active constituents. [8,9] For example, 11-keto-b-boswellic acid (KBA), acetyl-11-keto-b-boswellic acid (AKBA) and b-boswellic acid (BBA) have shown to inhibit 5-lipoxygenase and microsomal prostaglandin E synthase-1 or the serine protease cathepsin G. [10] Curcumin is a natural polyphenol, also a principal curcuminoid derived from the tuberous rhizomes of turmeric (Curcuma Longa Linn; Family: Zingiberaceae, Genus: Curcuma). [11] It has exhibited a number of biological activity including anti-inflammatory and antineoplastic potential [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Boswellia serrata, a medicinal plant of family Burseraceae, has been widely used in traditional medicine to treat various chronic inflammatory diseases such as osteoarthritis, chronic bowel diseases, arthritis, and asthma [10,11]. B. serrata extracts have multiple pharmacological properties, including anticancer, antidiabetic, immunomodulatory, antioxidant, and antiinflammatory activities [12][13][14]. In addition to the aforementioned pharmacological properties, the neuroprotective effects of B. serrata extracts under different conditions have been documented.…”
mentioning
confidence: 99%
“…In the present study, KBA (▶ Fig. 1) was selected because it is one of the major constituents in the triterpenoid fraction of the extract [14]. Furthermore, the efficacy of KBA in the CNS has been evaluated, including its distribution in the brain [22] and neuroprotective effects [23].…”
mentioning
confidence: 99%